The Economics of climate change in Latin America and the Caribbean : paradoxes and challenges of sustainable development (UN ECLAC SantiagoCL, 2014)
Presents the available evidence regarding global warming and estimates of the potential impacts on the region. Reviews adaptation measures and their potential costs. Looks at global and regional greenhouse gas emissions. Discusses the importance of moving towards a more balanced public/private matrix in order to improve quality of life and combat climate change , looking in particular at trends in consumption patterns with a focus on transportation needs. Presents conclusions.
Includes an overview.